2023
DOI: 10.1021/acs.jpcc.3c00404
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Atomic Diffusion in Surface and Bulk CuO via Neural Network-Based Molecular Dynamics

Abstract: Understanding the atomic diffusion process of a metal oxide helps with the design of more effective oxygen carriers for chemical looping with oxygen uncoupling (CLOU). Herein we investigated the atomic diffusion process in both slab and bulk CuO with varying oxygen vacancy (V O ) under CLOU conditions using density functional theory (DFT) calculations and molecular dynamic (MD) simulation based on the neural network (NN) potential. Although the diffusions of both the Cu and the O atoms are important for the sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 50 publications
(74 reference statements)
0
3
0
Order By: Relevance
“…Figure A presents the high-resolution Cu 2p XPS profile of cp -CuO/CF and cpc -CuO/CF. As compared to that in cp -CuO/CF, the Cu 2+ peak in cpc -CuO/CF shifted to lower energy (Cu 2p 3/2 , from 933.8 to 933.4 eV; Cu 2p 1/2 , from 953.6 to 953.1 eV), implying more O V in cpc -CuO/CF. , As for the O 1s spectra in Figure B, the peaks centered at 529.7 and 529.5 eV were ascribed to the lattice oxygen species (O Latt ), while the peaks observed at 531.3 and 532.3–532.8 eV were attributed to the surface adsorbed oxygen species (O Ads ) and adsorbed H 2 O groups (O Water ). Notably, the ratio of O Ads /O Latt over cpc -CuO/CF (3.80) was much higher than that of cp -CuO/CF (2.74), proving more surficial O V on cpc -CuO/CF (Table S2). Second, the EPR spectroscopy was used to validate the existence and relative content of O V in cpc -CuO/CF and cpc -CuO/CF.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Figure A presents the high-resolution Cu 2p XPS profile of cp -CuO/CF and cpc -CuO/CF. As compared to that in cp -CuO/CF, the Cu 2+ peak in cpc -CuO/CF shifted to lower energy (Cu 2p 3/2 , from 933.8 to 933.4 eV; Cu 2p 1/2 , from 953.6 to 953.1 eV), implying more O V in cpc -CuO/CF. , As for the O 1s spectra in Figure B, the peaks centered at 529.7 and 529.5 eV were ascribed to the lattice oxygen species (O Latt ), while the peaks observed at 531.3 and 532.3–532.8 eV were attributed to the surface adsorbed oxygen species (O Ads ) and adsorbed H 2 O groups (O Water ). Notably, the ratio of O Ads /O Latt over cpc -CuO/CF (3.80) was much higher than that of cp -CuO/CF (2.74), proving more surficial O V on cpc -CuO/CF (Table S2). Second, the EPR spectroscopy was used to validate the existence and relative content of O V in cpc -CuO/CF and cpc -CuO/CF.…”
Section: Resultsmentioning
confidence: 90%
“…Figure S9I showed the HR-TEM image of cp -CuO/CF, and the exposable crystal faces of CuO in cp -CuO/CF were (11̅1̅), (111), and (200), which was the same with that of cpc -CuO/CF, indicative of the negligible effect of CuO facets on FDCA production. Recently, the reported work showed that the activity of CuO could be modulated by its surficial O V . Along this line of thinking, we further examined the electronic states and surficial defects of CuO in both the cp -CuO/CF and cpc -CuO/CF.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation